"The Ripple Effect": The influence of social support on participation in a small workplace health promotion program. (29th June 2021) - Bell, Alexandra; Barrett, Norma; Lamaro Haintz, Greer
Abstract: Issue addressed: Workplaces are key settings for health promotion. There is limited evidence pertaining to workplace health promotion [WHP] in Australian small and medium enterprises [SMEs], particularly in regional areas. This qualitative study explored employee perceptions of a pilot workplace health promotion program, LifeMAP, conducted in a small health service enterprise in regional Victoria 2014‐2017, including facilitators of participation and perceived benefits of participation. Method: Ten LifeMAP participants were recruited using convenience sampling. Individual semi‐structured interviews (n = 7) and one focus group (n = 3) were conducted between August and September 2017. Data were analysed inductively and thematically to elicit emergent themes. Results: Social support emerged as the overarching theme influencing participation in LifeMAP, and a perceived benefit of participation. Using FitBits® and setting exercise challenges enabled social support to be fostered through role modelling, staff collegiality and community. There may be gendered differences in the experiences of role modelling in WHP. Conclusions: This SME, and others like it, often feature high levels of employee social connectedness, with a strong workplace and community networks. Social support is a critical influence in social connectedness which needs to be considered and incorporated into the design, implementation and evaluation of WHP programs as a means of overcoming WHP recruitment and participation challenges in regional SMEs. So what?: The identification of social support as a key factor for WHP participation and employee satisfaction is a valuable finding providing insight into how similar programs may be better designed and implemented to enhance WHP program recruitment and retention.